Expression of sex hormone receptors in juvenile angiofibromas and antiproliferative effects of receptor modulators. Issue 11 (13th January 2014) - Schick, Bernhard; Dlugaiczyk, Julia; Wendler, Olaf
Abstract Background Predilection of juvenile angiofibromas in adolescent boys has prompted the hypothesis of hormone‐dependent tumor growth. However, knowledge on expression and function of sex hormone receptors in juvenile angiofibromas is still sparse and inconsistent. Methods Transcript and protein expression of sex hormone receptors in juvenile angiofibromas was studied by quantitative reverse transcriptase–polymerase chain reaction (qRT‐PCR) and immunohistology/fluorescence. A bromodeoxyuridine assay was used to assess the antiproliferative effects of flutamide (androgen receptor antagonist) and tamoxifen (estrogen receptor modulator). Results Significantly increased transcript levels were observed for androgen receptor, estrogen receptor α, follicle‐stimulating hormone receptor, and luteinizing hormone receptor in juvenile angiofibromas versus the stroma of nasal mucosa. Estrogen receptor β and progesterone receptor mRNA levels were low and similar for both tissues. Estrogen receptor α protein was detected in juvenile angiofibroma tumors and mesenchymal cell lines. Flutamide and tamoxifen inhibited proliferation of cultured juvenile angiofibroma mesenchymal cells. Conclusion These findings contribute to the understanding of juvenile angiofibroma pathophysiology and offer novel therapeutic options. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1596–1603, 2014